Is hypoperfusion an important cause of strokes?: If so, how? - Caplan, Louis R.; Wong, Ka Sing; Gao, Shan; Hennerici, Michael G. (Cerebrovascular diseases, 2006)
Traditionally hypoperfusion and embolism are considered separate important causes of stroke in patients with arterial occlusive disease. However, although hypoperfusion and embolism differ in mechanisms and location, they generally coincide in severe obstructive lesions and cause washout disturbances of embolism in low perfusion territories distal to stenosis. Unless the collateral blood supply is sufficient to prevent ischemia, multiple remote spot-like infarctions occur within the hypoperfused brain territory. In border-zone distributed infarction - long suspected to result from hemodynamic compromise alone - complementary interaction of embolisation and hypoperfusion territories has to be considered. Thus hypoperfusion with embolism or embolism alone are the most common explanations for stroke, the former often associated with less severe clinical deficits than the latter.